Hotel for dogs [videorecording (DVD)] - Lowell, Jeff; Schooley, Bob; Duncan, Lois, 1934-2016; Roberts, Emma, 1991-; Austin, Jake T. (Jake Toranzo), 1994-; Cheadle, Don; Kudrow, Lisa (Paramount, 2017)
When Andi and her younger brother Bruce find themselves in a new foster home with a 'no pets' policy, they must put their heads together to find a new home for Friday, their dog. When they stumble upon an abandoned hotel, they transform it into a magical dog paradise for Friday, as well as all the strays in the city.